2013
DOI: 10.1186/1471-2474-14-312
|View full text |Cite
|
Sign up to set email alerts
|

Knee loading reduces MMP13 activity in the mouse cartilage

Abstract: BackgroundModerate loads with knee loading enhance bone formation, but its effects on the maintenance of the knee are not well understood. In this study, we examined the effects of knee loading on the activity of matrix metalloproteinase13 (MMP13) and evaluated the role of p38 MAPK and Rac1 GTPase in the regulation of MMP13.MethodsKnee loading (0.5–3 N for 5 min) was applied to the right knee of surgically-induced osteoarthritis (OA) mice as well as normal (non-OA) mice, and MMP13 activity in the femoral carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 33 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…Valve remodeling and development is regulated by coordinated actions between matrix metalloproteinase and a disintegrin and metalloproteinase with thrombospondin motifs families of zinc metalloproteinases . Studies have shown a role for Rac1 in the regulation of extracellular matrix degradation along with matrix metalloproteinase expression and activity . The thickened Rac1 SHF aortic valve leaflets along with decreased valve cell density and increased deposition of glycosaminoglacans observed in this study strongly suggest defects in valvular extracellular matrix degradation and remodeling.…”
Section: Discussionsupporting
confidence: 60%
“…Valve remodeling and development is regulated by coordinated actions between matrix metalloproteinase and a disintegrin and metalloproteinase with thrombospondin motifs families of zinc metalloproteinases . Studies have shown a role for Rac1 in the regulation of extracellular matrix degradation along with matrix metalloproteinase expression and activity . The thickened Rac1 SHF aortic valve leaflets along with decreased valve cell density and increased deposition of glycosaminoglacans observed in this study strongly suggest defects in valvular extracellular matrix degradation and remodeling.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, in adult articular tissues, p38 is known to play an important role in the inflammatory process (Joos et al 2009), and some evidence suggests that p38 is a major signaling molecule in the induction of MMP-13 and the activity of p38 can have negative effects on cartilage matrix maintenance (Julovi et al 2011;Mengshol et al 2000;Pei et al 2006). In addition, moderate mechanical stress such as knee loading reduces MMP-13 activity through the p38 MAPK signaling pathway in normal articular cartilage (Hamamura et al 2013). Therefore, we speculated that LIPUS inhibited phosphorylation of p38 in OA chondrocytes, but facilitated phosphorylation of p38 in normal chondrocytes to promote adaptation to a moderate mechanical stress.…”
Section: Discussionmentioning
confidence: 97%
“…Mechanical loading and joint health have a unique relationship. Low levels of mechanical loading, such as mild exercise, can benefit cartilage by preventing injury‐induced cartilage degradation, maintaining thicker cartilage, and increasing proteoglycan synthesis . However, higher levels of loading can lead to cartilage degradation by decreasing proteoglycan synthesis, inducing chondrocyte apoptosis, and rupturing critical stabilizing ligaments .…”
mentioning
confidence: 99%